Phosphatase-regulated recruitment of the spindle- and kinetochore-associated (Ska) complex to kinetochores - Sivakumar, Sushama (Biol Open, 2017)
Kinetochores move chromosomes on dynamic spindle microtubules and regulate signaling of the spindle checkpoint. The spindle- and kinetochore-associated (Ska) complex, a hexamer composed of two copies of Ska1, Ska2 and Ska3, has been implicated in both roles. Phosphorylation of kinetochore components by the well-studied mitotic kinases Cdk1, Aurora B, Plk1, Mps1, and Bub1 regulate chromosome movement and checkpoint signaling. Roles for the opposing phosphatases are more poorly defined. Recently, we showed that the C terminus of Ska1 recruits protein phosphatase 1 (PP1) to kinetochores. Here we show that PP1 and protein phosphatase 2A (PP2A) both promote accumulation of Ska at kinetochores. Depletion of PP1 or PP2A by siRNA reduces Ska binding at kinetochores, impairs alignment of chromosomes to the spindle midplane, and causes metaphase delay or arrest, phenotypes that are also seen after depletion of Ska. Artificial tethering of PP1 to the outer kinetochore protein Nuf2 promotes Ska recruitment to kinetochores, and it reduces but does not fully rescue chromosome alignment and metaphase arrest defects seen after Ska depletion. We propose that Ska has multiple functions in promoting mitotic progression and that kinetochore-associated phosphatases function in a positive feedback cycle to reinforce Ska complex accumulation at kinetochores.